Susceptibility of Escherichia coli isolates from mares to ozonated sunflower oil - Gabriel Souza dos Santos; Arthur Azevedo Perpétuo; Tiago Santos Fonseca; Marcus Vinícius Dias-Souza (International Journal of Basic and Applied Science, 2022)
Sunflower oil is known for its therapeutic properties and culinary use. It is an important alimentary source of tocopherol and unsaturated fatty acids, and is used especially for wound healing. Studies indicate that it also has antimicrobial potential. The ozonation of oils of vegetable sources has been explored as a way to enhance their therapeutic properties; however, studies that provide evidence of such benefits are still lacking. In the field of veterinary medicine, such data are even more scarce. In this study, the antimicrobial activity of ozonated sunflower oil was compared to that of non-ozonated oil, in an in vitro system. We used clinical isolates of Escherichia coli, obtained from intrauterine lavages of mares with endometritis. Tests were conducted using the minimum inhibitory concentration method. Our data open doors for discussion on the use of sunflower oil, with or without ozone treatment, for therapeutic purposes in veterinary medicine.